2020
DOI: 10.1093/phe/phaa003
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Phage: Ethical Challenges of Using Phage Therapy to Treat Bacterial Infections

Abstract: For over a century, scientists have run experiments using phage viruses to treat bacterial infections. Until recently, the results were inconclusive because the mechanisms viruses use to attack bacteria were poorly understood. With the development of molecular biology, scientists now have a better sense of how phage work, and how they can be used to target infections. As resistance to traditional antibiotics continues to spread around the world, there is a moral imperative to facilitate research into phage the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, this has not been replicated in the West, due to factors including the widespread use of antibiotics and the lack of clinical guidelines from the regulatory bodies involved, due to ethical and safety concerns regarding the development of phage resistance by the bacteria in patients [18]. This has meant that phage therapy is mostly used as a last resort when all antibiotics have failed [19]. Most of the successful studies that have been conducted tended to utilize phage cocktails rather than a single phage, with the most successful therapies being those that combined phage cocktails (where two or more phages are used) in combination with antibacterial chemicals [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, this has not been replicated in the West, due to factors including the widespread use of antibiotics and the lack of clinical guidelines from the regulatory bodies involved, due to ethical and safety concerns regarding the development of phage resistance by the bacteria in patients [18]. This has meant that phage therapy is mostly used as a last resort when all antibiotics have failed [19]. Most of the successful studies that have been conducted tended to utilize phage cocktails rather than a single phage, with the most successful therapies being those that combined phage cocktails (where two or more phages are used) in combination with antibacterial chemicals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, although the idea of not developing resistant bacterial strains against BT was one of the advantages, however, the emergence of bacterial resistance is possible owing to the ability of bacteria to develop various mechanisms to prevent phage activity such as hiding, loss of receptor, producing factors which inhibit phage replication [ 47 , 53 ]. This was observed with lysogenic phages, as these phages integrate into bacterial chromosomes instead of destroying them, which could possibly lead to bacteria expressing new properties related to resistance development against other phages; furthermore, when lysogenic phages integrate into bacterial cells, they can cause those bacteria to develop antibiotics resistance by acting as act as vehicles for genetic material horizontal exchange [ 4 , 9 , 47 , 50 ]. Third, another possible challenge when determining the sensitive bacteriophages against certain bacteria is the site and method of obtaining bacterial cultures; in a pilot study by Doub et al [ 14 ] aiming at evaluating if bacteriophage activity is the same across all in vivo PJI environments, three patients diagnosed with S. aureus PJI by arthrocentesis cultures and at least three deep tissue cultures, the authors tested these isolates against various BPs, they reported heterogenic bacteriophage activity depending on the type of cultures taken (arthrocentesis vs. deep tissues), the authors recommended that choosing the appropriate BT should be based on both arthrocentesis and multiple deep tissue cultures to guarantee bacteriophage activity across all in vivo environment.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, phage therapy has been available almost only for “compassionate use” [ 91 , 97 , 98 ] (i.e., when need is great and all else has failed) and particularly for treatment of pan-drug-resistant infections or otherwise following antibiotic treatment failures (i.e., with phages serving as salvage therapies). Despite the recent progress in many aspects of the development of phage therapy, the introduction of phages into the clinic still faces major obstacles [ 147 , 218 , 219 ], and this is particularly from unresolved regulatory questions [ 220 ].…”
Section: Continuing Challenges For Phage Therapymentioning
confidence: 99%
“…Further complicating the broader implementation of phage therapy are economic uncertainties associated with phage therapy development. While biotech companies often succeed in translating basic research into profitable clinical applications [ 219 ], investment into phage therapy nonetheless raises many concerns, not least of which is the limited patentability of phages, along with unmodified enzybiotics [ 277 ], as “natural phenomena” or “product[s] of nature” [ 278 ]. US patents covering the use of natural phages in therapy nevertheless have been granted [ 279 ], many of them claiming that specific phage cocktails are essential to reduce the risk of resistance development by targeted bacteria [ 280 ].…”
Section: Continuing Challenges For Phage Therapymentioning
confidence: 99%